The Public Health Implications of the Use and Misuse of Tobacco among the Aboriginals in Canada - Orisatoki, Rotimi (Glob J Health Sci, 2013)
Tobacco smoking among the Aboriginal populations is a major public health issue in Canada. It remains a major contributory risk factor to the poor health status as well as years of potential life lost seen among the indigenous people. The use of tobacco has a spiritual importance to the people as a means of making connection to the Creator, but unfortunately tobacco smoking has taken a recreational aspect which has little or no connection with Aboriginal spirituality. The non-traditional use of tobacco is believed by the Elders to be disrespectful to the Aboriginal culture and traditional way of life. There is an increase in rate of use of smokeless tobacco as well as smoking of tobacco among the youth with increase in percentage among females. There are socioeconomic implications as well as adverse health effects of the misuse of tobacco on the Aboriginal people that need to be addressed. The healthcare professionals have a unique role in helping patients to reduce tobacco use within the community through programs that are culturally sensitive and relevant. Successful strategies requires general support from the community and it is very important that some of that support comes from community leaders, including spiritual, professional, administrative and elected policy makers.